Response to ‘The National Planning Policy Framework and Archaeology: A Discussion’ - Judith Rosten (Papers from the Institute of Archaeology, 2013)
The CPRE believes good land-use planning is the unsung hero of environmental protection and, as defined by the National Policy Planning Framework (NPPF), the environment includes the natural, built and historic environment, of which archaeology is a part. The historic environment cons of the NPPF have been set out in the article and, in terms of archaeology in particular, the move away from public and research benefits is a step back. But there are also positives that can be taken from the changes.
Keywords: National Planning Policy Framework; planning; development